Introducción: En torno a la fábula esópica medieval - María Luzdivina Cuesta Torre (Atalaya)
This is an introduction to the monograph and the main research areas of for the “Aesop’s Fables in Spanish Literature in the Fourteenth Century” project (FFI2012-32265). Research into Spanish fables written during The Middle Ages usually includes the fables as exemples which denies fables the status as an entity in themselves.